Preventing Undesirable Structure Flexibility in Pyromellitate Metal Organic Frameworks. Issue 26 (27th May 2020) - Hayes, Oliver G.; Warrender, Stewart J.; Cordes, David B.; Duncan, Morven J.; Slawin, Alexandra M. Z.; Morris, Russell E.
Abstract : Removal of coordinated water molecules from the porous Zn‐pyromellitate metal organic framework Zn5 (OH)2 (PMA)2 (H2 O)4 · x H2 O (PMA = pyromellitic acid or 1, 2, 4, 5‐benzene tetracarboxylic acid) should generate coordinatively unsaturated metal sites suitable for gas adsorption. However, reports of instability towards dehydration have restricted the study and utility of this MOF. Here we examine in more detail the nature of the structural transformation that occurs upon dehydration. This study reveals that a fully reversible crystalline‐crystalline transformation from a porous to a non‐porous homologue takes place, proceeding through a partially dehydrated intermediate. We show that doping the structure with Ni 2+ ions at greater than 30 % prevents structural rearrangement, thereby maintaining porosity, and rendering the material effective for gas (nitric oxide) adsorption applications. These results indicate that doping can be an effective means to increase the utility of otherwise unserviceable structures. Abstract : Doping of a Zn‐pyromellitic acid‐based metal organic framework with Ni prevents a detrimental, reversible, crystalline‐crystalline transformation occurring on dehydration and permits delivery of the medically useful gas nitric oxide from the previously unserviceable material.